THE ROLE OF ACCENTS IN BATU BARA MALAY COMMUNICATION - Doni Efrizah (Universitas Islam Sumatera Utara, 2023)
This research aims to explore the role of accent in Batu Bara Malay communication. Batu Bara Malay is a dialect of Malay spoken in Batu Bara area of North Sumatra, Indonesia and has unique phonological characteristics. This research is also to identify the characteristics of the accent in Batu Bara Malay, understand its impact in daily communication, and investigate the role of accent in communication. This research uses a combination approach of case study and phonological analysis. The data were collected through interviews with native Batu Bara Malay speakers, observations of daily communication, and analysis of voice recordings. The research results show that Batu Bara Malay has distinctive accent characteristics, including phonological variations in the use of phonemes and intonation that are different from the standard Malay or Indonesian. In the context of daily communication, the use of accents in Batu Bara Malay affects understanding and expression. Differences in accents in informal conversation and formal communication were also identified. Social and cultural factors play a role in accent variation. This research contributes to further understanding of Batu Bara Malay and the importance of maintaining this dialect. The results can be used as a basis for efforts to preserve language and culture in Batu Bara Malay community.